2020
DOI: 10.1002/ijfe.2169
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal episodes in the Economic and Monetary Union: Elasticities and non‐Keynesian effects

Abstract: We estimate short-and long-run elasticities of private consumption for fiscal instruments, using a fixed-effects model for the 19 Euro area countries during the period of 1960-2017, to assess how fiscal elasticities vary during fiscal episodes. According to the results, positive 'tax revenue' elasticities indicate that consumers have Ricardian behaviour, whereby they perceive an increase in taxation to be a sign of future government spending. 'social benefits' appear to have a non-Keynesian effect on private c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Numerous studies conducted from 1990 to 2016 revealed that economic growth and government expenditure have a positive relationship with each other. Optimising government spending is characterised by a crowding-in effect with economic growth (Afonso & Leal, 2020;Alshammary et al, 2020). In a similar vein, the study conducted by Abotsi (2021) utilised a panel comprising 95 countries to examine the correlation between fiscal policy and investment over the period spanning from 1970 to 2008.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies conducted from 1990 to 2016 revealed that economic growth and government expenditure have a positive relationship with each other. Optimising government spending is characterised by a crowding-in effect with economic growth (Afonso & Leal, 2020;Alshammary et al, 2020). In a similar vein, the study conducted by Abotsi (2021) utilised a panel comprising 95 countries to examine the correlation between fiscal policy and investment over the period spanning from 1970 to 2008.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notwithstanding the relevance of fiscal policy sustainability, analyses on the so-called expansionary fiscal consolidations has received much attention. The macroeconomic effects of such fiscal consolidations, related with the notion of non-Keynesian effects, are well described in the literature (see, for instance, von Hagen and Strauch, 2001, van Aarle and Garretsen, 2003, Giudice et al, 2007, Alesina et al, 2015, Alesina et al, 2019, Afonso and Leal, 2020, Afonso et al, 2021. In addition to looking at the non-Keynesian effects, the literature has devoted time and effort to identify fiscal episodes, i.e., periods when the change in the cyclically adjusted primary balance is greater than an ad-hoc positive threshold value (contractionary "discretionary" fiscal policy) or lower than a negative threshold value (expansionary "discretionary" fiscal policy).…”
Section: Introductionmentioning
confidence: 99%
“…This school of thought assumes that the economy has an excess capacity and that there are also liquidityconstrained individuals in the economy. Therefore, fiscal policy can stimulate aggregate demand through private consumption, which can induce the labor market and activate private investment to respond quickly to fiscal shocks (Brinca et al, 2016;Afonso -Leal, 2022). However, fiscal adjustments are expected to reduce aggregate demand and, thus, output.…”
Section: Literature Reviewmentioning
confidence: 99%